2010
DOI: 10.1097/psy.0b013e3181de7ff8
|View full text |Cite
|
Sign up to set email alerts
|

It's More than Sex: Exploring the Dyadic Nature of Sleep and Implications for Health

Abstract: Sleep is a critical health behavior and one that is typically shared between husbands and wives or romantic partners. However, the science of sleep has traditionally conceptualized and evaluated sleep at the level of the individual. Considering the social context of sleep represents a significant shift in sleep research and also offers a critical opportunity for investigating sleep as a novel pathway linking close relationships with health. The purpose of this review is to integrate research that focuses on ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
201
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(217 citation statements)
references
References 117 publications
9
201
2
4
Order By: Relevance
“…Graduate students were more likely to be in a committed relationship and although the current study did not inquire about sleep patterns, Troxel's (2010) review indicates that those with a sleep partner frequently report better sleep patterns than those who do not have a sleep partner or when the sleep partner is not present. Similarly, others (Cacioppo et al, 2002) have found that lonely individuals have poor sleep patterns compared to those less lonely.…”
Section: Discussionmentioning
confidence: 95%
“…Graduate students were more likely to be in a committed relationship and although the current study did not inquire about sleep patterns, Troxel's (2010) review indicates that those with a sleep partner frequently report better sleep patterns than those who do not have a sleep partner or when the sleep partner is not present. Similarly, others (Cacioppo et al, 2002) have found that lonely individuals have poor sleep patterns compared to those less lonely.…”
Section: Discussionmentioning
confidence: 95%
“…It has been suggested that, from an evolutionary perspective women may rely on their larger, more dominant male partner to provide safety and protection. Thus, it is plausible that if a couple are experiencing relationship difficulties, the woman may not experience the safety and security necessary for optimal sleep (Troxel 2010). Evolutionarily this may seem plausible; however, males may also require feelings of safety and security emotionally for optimum sleep.…”
Section: Specific Nonshared Environmental Influence: Relationship Satmentioning
confidence: 99%
“…[7][8][9] Because alcohol dependence often cooccurs with other psychiatric disorders, 4 it is unclear whether individuals who present with comorbid alcohol dependence and other psychiatric conditions are more likely to experience sleep disturbances than those with alcohol dependence alone. Moreover, there is an association between sleep parameters and various socio-demographic factors (eg, age, 10 race/ethnicity, 11 and marital status 12 ) in relatively healthy participants, which may also confound this relationship.…”
Section: Introductionmentioning
confidence: 99%